Interpreting WTO agreements : problems and perspectives - Qureshi, Asif H. (Cambridge University Press, 2015)
"The jurisprudence of the World Trade Organization (WTO) is replete with references to Articles 31-2 of the Vienna Convention (VC) on the Law of Treaties. This gospel for interpretation is often the starting-point of judgments in the WTO. Its use in the WTO became established with the Appellate Body (AB) decision in the US-Gasoline case wherein it was pointed out that the general rule of interpretation set out in Article 31 of the VC had attained the status of a rule of customary or general international law. As such, it forms part of the 'customary rules of interpretation of public international law' which the Appellate Body has been directed, by Article 3(2) of the DSU [Understanding on Rules and Procedures Governing the Settlement of Disputes], to apply in seeking to clarify the provisions of the General Agreement and the other 'covered agreements' of the Marrakesh Agreement Establishing the World Trade Organization .... That direction reflects a measure of recognition that the General Agreement is not to be read in clinical isolation from public international law. (Footnotes omitted) This statement is often religiously cited in other WTO cases"--